Post-Communist Mafia State: The Case of Hungary - Magyar, Bálint (Amsterdam University Press, 2016)
Having won a two-third majority in Parliament at the 2010 elections, the Hungarian political party Fidesz removed many of the institutional obstacles of exerting power. Just like the party, the state itself was placed under the control of a single individual, who since then has applied the techniques used within his party to enforce submission and obedience onto society as a whole. In a new approach the author characterizes the system as the ‘organized over-world’, the ‘state employing mafia methods’ and the ’adopted political family', applying these categories not as metaphors but elements of a coherent conceptual framework.The actions of the post-communist mafia state model are closely aligned with the interests of power and wealth concentrated in the hands of a small group of insiders. While the traditional mafia channeled wealth and economic players into its spheres of influence by means of direct coercion, the mafia state does the same by means of parliamentary legislation, legal prosecution, tax authority, police forces and secret service. The innovative conceptual framework of the book is important and timely not only for Hungary, but also for other post-communist countries subjected to autocratic rules.